Synthesis of Methyl 2-((4R)-3-Acryloyl-4-phenyloxazolidin-2-yl)acetates - Hugo Pilotzi Xahuentitla; Jesús Guadalupe Ortega Montes; Dino Hernán Gnecco Medina; Joel Luis Terán Vázquez; Emanuel Hernández Núñez; Maria Laura Orea Flores (Molbank)
The chiral oxazolidine moiety is an important core in asymmetric synthesis due to its ability to participate in various stereoselective chemical reactions and because it forms part of more complex and important active compounds. Therefore, in this letter we report a convenient diastereoselective and practical strategy for the synthesis of chiral methyl 2-((4R)-3-acryloyl-4-phenyloxazolidin-2-yl)acetates, starting from (R)-(–)-2-phenylglycinol and methyl propiolate, which were obtained via two simple chemical and stereoselective reactions.